Implementing a Self-Checking Profibus Slave - Margrit Reni Krug (2000)
This work presents the study and preliminary results of the high level implementation of a self-checking Profibus slave. From an existing VHDL description of the device, a test strategy was studied and implemented, so that the whole circuit has embedded test structures capable to perform at-speed test of the slave. In this paper, we show the used test strategies and implementation results achieved from a synthesis process in a FPGA environment.